2009
DOI: 10.1055/s-2008-1039114
|View full text |Cite
|
Sign up to set email alerts
|

Intravertebrale Druckentwicklung bei der Vertebroplastie – Eine anatomische In-vitro-Untersuchung

Abstract: The 13.6-fold increase in intravertebral body pressure caused by cement injection during percutaneous vertebroplasty in comparison to the baseline venous pressure for the ascending lumbar vein might be one possible cause of the high rate of extravasation of bone cement reported in the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…These changes differ from the changes described on bone, where the necrosis is more frequent. This could be because liquid cement may require less pressure to distribute itself, inside soft tissue than inside the bone; in fact, an in-vitro study in cadaveric vertebras showed an increase of 13.6 folds on average over the base line of bone pressure during the injection of polymethylmethacrilate [28]. …”
Section: Discussionmentioning
confidence: 99%
“…These changes differ from the changes described on bone, where the necrosis is more frequent. This could be because liquid cement may require less pressure to distribute itself, inside soft tissue than inside the bone; in fact, an in-vitro study in cadaveric vertebras showed an increase of 13.6 folds on average over the base line of bone pressure during the injection of polymethylmethacrilate [28]. …”
Section: Discussionmentioning
confidence: 99%